Why Women Became the Enemy of Democracy in Poland? The Illiberal Regime's Response to the Women' Rights Movement - Rezmer-Płotka, Kamila (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2022)
After the political transformation in Poland, abortion was first regulated by the Law of 7 January 1993, Protection of the Human Fetus and Conditions Permitting Pregnancy Termination. Since then, attempts have been made to change the existing regulation. However, it was in 2016 that there were nationwide protests against changes to abortion provisions, and then in 2020, when the constitutional court ruling limited the possibility of termination of pregnancy in Poland. These protests can be seen in the context of the process of neo-militant democracy rule implementation, that is, the taking over the characteristics of non-democratic regimes by existing democracies under the cover of the regime self-preservation. The aim of this article is to identify and explain the government’s attitude towards women as an enemy of democracy at the institutional level during the two waves of protests. The study shows that during the period considered, restrictions specific to neo-militant democracies in the area of assembly and association, speech and press and restrictions on religious freedom were imposed in order to limit the activity of protesters viewed as enemies of the democratic system.

Po transformacji ustrojowej w Polsce aborcja została po raz pierwszy uregulowana ustawą z dnia 7 stycznia 1993 r. o ochronie płodu ludzkiego i warunkach dopuszczalności przerywania ciąży. Od tego czasu podejmowane są próby zmiany dotychczasowego rozporządzenia. Jednak dopiero w 2016 r. doszło do ogólnopolskich protestów przeciwko zmianom w przepisach dotyczących aborcji, a następnie w 2020 r., kiedy orzeczenie Trybunału Konstytucyjnego ograniczyło możliwość przerywania ciąży w Polsce. Protesty te można rozpatrywać w kontekście procesu wdrażania rządów demokracji opancerzonej, czyli przejmowania cech niedemokratycznych reżimów przez istniejące demokracje pod przykrywką samozachowania reżimu. Celem artykułu jest zidentyfikowanie i wyjaśnienie stosunku władz do kobiet jako wroga demokracji na poziomie instytucjonalnym podczas obu fal protestów. Z badania wynika, że w badanym okresie specyficzne dla demokracji opancerzonej ograniczenia w obszarze zgromadzeń i stowarzyszeń, wypowiedzi i prasy oraz ograniczenia wolności wyznania zostały wprowadzone w celu ograniczenia aktywności protestujących postrzeganych jako wrogowie systemu demokratycznego.
Dlaczego kobiety stały się wrogiem demokracji w Polsce? Reakcja reżimu antyliberalnego na Ruch na rzecz Obrony Praw Kobiet
Keywords: neo-militant democracy; abortion; protests; woman’s rights; illiberal; contentious politics; contention; demokracja opancerzona; aborcja; protesty; prawa kobiet; nieliberalność; kontestacja polityczna; spór